KOMPOSISI VEGETASI PAKAN JULANG SULAWESI (Ryticeros cassidix) DI KAWASAN CAGAR ALAM PANGI BINANGGA KECAMATAN PARIGI MAUTONG - Hanapi Hanapi; Adam Malik; Sustri Sustri (Universitas Tadulako, 2016)
Hornbill (Rhyticeros cassidix) is Sulawesi endemic bird and fruit eater bird. The fruits that eaten by hornbill categorized as small fruits and in large number involved ficus species and stoneseeds, it is non-ficus species. Hornbill bird also easy to be recognized by having big beak and body. And commonly the exist bird habitats relatively good by founding some birds species as an indicator of good forest ecosystem. The aim of the research was to find out the Woof Vegetation of Hornbill (Ryticeros cassidix) bird in the Natural Conservation Area in Pangi Binangga village Parigi Mautong District Central Sulawesi that began on November up to the month of Desember 2014. By knowing the woof vegetation and the birds habitat, it is important to keep their preservation because the bird is Sulawesi endemic. The result of the research that conducted in Natural Preservation Area of Pangi Binangga found the vegetation composition of Hornbill (Ryticeros cassidix ) bird.The analysis result of vegetation composition by applying Importance Rate Index (IRI) when Hornbill in the primary forest in Natural Conservation Area of Pangi Binangga: The highest Importance Rate Index on Tree species Level (Pometia Pinata J.R Forst) with rate of 35.1%, onPole species level (Canarium asperum) with rate of 53.4%, on pile species level (Pinanga sp) with rate of 25.5% and on seeding species level (Memordica cochinchinensis) with rate of 23.6%. By using transect path observation plot of 100 meter, it was found some Woof Vegetations of Hornbill in the Natural Conservation Area of Pangi Binangga, they were; Beringin tree (Ficus benjamina) that had rate of 18.7 %, Ebony (Diospyros celebica Bakh) that had rate of 14.8 %, Canary nut (Canariu asperum) with rate of 6.07 % and Benunu (Ficus annulata blume) with rate of 5.50 %.Keywords : Vegetation composition, Woof of Hornbill (Ryticeros cassidix)bird